Precise Shoe-Material Cutting Using Image-Based Die Cutter Calibration for Punching Machine Tools - Su, Chia-Hsiang; Lin, Horng-Horng (Manufacturing Technology Journal, 2025)
This paper proposes a set of stable auxiliary positioning modules for die-cutting shoe material by means of image-based die-cut calibration. Used in combination with a self-developed polygonal-object packing system for shoe-material cutting, the punching machine tool can automatically cut accurately, stably, and efficiently with the highly integrated hardware and software. In particular, the packing of the shoe material is based on the contour of the die-cut mold vector, and the object-dilation method is used to maintain a fixed gap between the objects. Then, a search method is employed to calculate a compact packing of the die-cut contours. The center point and azimuth angle of the die-cut contours are determined through object packing by a heuristic search. The contours of this die-cut are projected directly onto the positioning module. The physical die-cut mold is aligned with the images, and then the die-bar is locked to complete the die positioning, which is synchronized with the packing system. This new die-cut calibration method is more accurate and reliable. Moreover, the error in the gap between the material and the die-cut was ±0.1 mm, which is in line with the development trend of automatic precision die-cutting.
Keywords: Die Cutter Calibration; Object Packing; Punching Machine Tools; Shoe Material Cutting